Repetitive Robot Behavior Impacts Perception of Intentionality and Gaze-Related Attentional Orienting - Abubshait, Abdulaziz; Wykowska, Agnieszka (Frontiers in Robotics and AI, 2020)
Gaze behavior is an important social signal between humans, as it communicates locations of interest. People typically orient their attention to where others look, as this informs about others’ intentions and future actions. Studies have shown that humans can engage in similar gaze behavior with robots, but presumably more so when they adopt the intentional stance towards them (i.e., believing robot behaviors are intentional). In laboratory settings, the phenomenon of attending towards the direction of others’ gaze has been examined with the use of the gaze-cueing paradigm. While the gaze-cueing paradigm has been successful in investigating the relationship between adopting the intentional stance towards robots and attention orienting to gaze cues, it is unclear if the repetitiveness of the gaze-cueing paradigm influences adopting the intentional stance. Here, we examined if the duration of exposure to repetitive robot gaze behavior in a gaze-cueing task has a negative impact on subjective attribution of intentionality. Participants performed a short, medium, or long face-to-face gaze-cueing paradigm with an embodied robot while subjective ratings were collected pre and post the interaction. Results show that participants in the long exposure condition had the smallest change in their intention attribution scores, if any, while those in the short exposure condition had a positive change in their intention attribution indicating that participants attributed more intention to the robot after short interactions. The results also show that attention orienting to robot gaze-cues was positively related to how much intention was attributed to the robot, but this relationship became more negative as the length of exposure increased. In contrast to subjective ratings, the gaze cueing effects increased as a function of the duration of exposure to repetitive behavior. The data suggest a tradeoff between the desired number of trials needed for observing various mechanisms of social cognition, such as gaze cueing effects, and the likelihood of adopting the intentional stance towards a robot.